Unification of the Graviatational and Electromagnetic Fields through Nonlinear Physics (Global Journal of Science Frontier Research, 2019)
The article reveals the similarities of the provides farther evidence that the gravitational field is a special type of weak nonlinear electromagnetic field (NEMF), which in attractor. Read the article to learn about the type, structure, and dynamics of this electromagnetic field, which manifests itself as relativity was used to describe holographic quantum matter, whi common roots of the gravitational and gravitational field can be modeled as a quantum matter, which indicates field is a quantum field. If so, quantum dynamic nonlinear electromagnetic fields (NEMF) (starting with elementary particles and everything in between).
Keywords: nonlinear electromagnetic fields; gravitational field; similarity of electromagnetic and gravitational